1997
DOI: 10.1002/19970505nt3
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of myristicin

Abstract: Myristicin, or methoxysafrole, is the principal aromatic constituent of the volatile oil of nutmeg, the dried ripe seed of Myristica fragrans. Myristicin is also found in several members of the carrot family (Umbelliferae). Several intoxications have been reported after an ingestion of approximately 5 g of nutmeg, corresponding to 1-2 mg myristicin/kg body weight (b.w.). Although these intoxications may be ascribed to the actions of myristicin, it is likely that other components of nutmeg may also be involved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 24 publications
2
58
0
Order By: Relevance
“…These results are in agreement to those psychopharmalogical effects published for myristicin, an analogue of sarisan (Shulgin 1966, Hallstrom & Thuvander 1997. It has been demonstrated that myristicin promotes CNS depressant effect besides an induction of the cytochrome P-450 system (Hallstrom & Thuvander 1997).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement to those psychopharmalogical effects published for myristicin, an analogue of sarisan (Shulgin 1966, Hallstrom & Thuvander 1997. It has been demonstrated that myristicin promotes CNS depressant effect besides an induction of the cytochrome P-450 system (Hallstrom & Thuvander 1997).…”
Section: Resultssupporting
confidence: 91%
“…It has been demonstrated that myristicin promotes CNS depressant effect besides an induction of the cytochrome P-450 system (Hallstrom & Thuvander 1997). Previous investigation with eugenol and safrole, arylpropanoid derivatives, showed that these compounds intervene in the cytochrome P-450 functions (Nagababu & Lakshmaiah 1994, Janiaud et al 1997.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-4. Myristicin concentration found in GN4 is close to maximum reported concentration (Hallström and Thuvander 1997), and on this basis, it can be stated that GN4 is a high-quality spice. Moreover, it was noticed that the results somehow correspond with relations of people abusing nutmeg, published on the Internet (see Supplementary material, section 2), as nutmeg from producers 4, 3 and sometimes 2 are recommended for giving the best psychoactive effects.…”
Section: Analysis Of Myristicin In Commercially Available Spicessupporting
confidence: 70%
“…Myristicin content in plant organs varies, depending on both growing and storage condition, and it can amount up to 13 mg per 1 g in the high-quality M. fragrans nut (nutmeg); it is also abundant in aril of the nut (mace) (Hallström and Thuvander 1997) and its pericarp (Choo et al 1999). Psychoactive effects usually develop after administration of at least 10 g of grounded nutmeg and include amphetamine-like effects and hallucinations (Ehrenpreis et al 2014).…”
Section: Introductionmentioning
confidence: 99%